The international criminal tribunal for the former Yugoslavia and the rule of law in international relations - Pupavac, Mladen (2003)
The aim of this study has been to explore the political and legal significance of the International Criminal Tribunal for the Former Yugoslavia, both within the territory of the former Yugoslavia and beyond. Within these parameters, the overall purpose of the study has been to examine, firstly, whether the ICTY has contributed to the restoration of peace and security in the territory of the former Yugoslavia, and secondly, whether, using the experience of the ICTY, it is reasonable to expect that the newly established International Criminal Court (ICC) will make a similar contribution to international peace and security and the rule of law in international relations more generally. Therefore, the academic aim of the thesis is to use the results of the empirical research on the ICTY as a basis for reasoned speculation about the ICC. In seeking to answer whether the ICTY has contributed to peace and security in the former Yugoslavia, the thesis analyses the cooperation of the actors within and outside the former Yugoslavia, both state and non-state, arguing that the ICTY has not achieved its main objective. Using the lessons of the ICTY, the thesis seeks to modify expectations about the potential of the ICC to contribute to the maintenance of international peace and security by helping to manage similar conflicts in the future. In answering whether the ICTY has contributed to the rule of law in international relations, the thesis has contextualised the ICTY within the history of similar attempts to use international law and international institutions to prohibit and/or regulate the use of force in international relations. The overall conclusion is that the ICTY has not achieved this goal either.